PENGARUH KOMUNIKASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA UNIVERSITAS PRIMAGRAHA DI KOTA SERANG - Priatna Wijaya (DESANTA (Indonesian of Interdisciplinary Journal), 2023)
The purpose of this study is to determine the Influence of Communication and Organizational Culture on Employee Performance at Primagraha University in Serang City. This study used a quantitative approach. The population in this study is 40 employees of Primagraha University. Because the population is less than 100, the author uses a saturated sample of the entire population to be sampled as many as 40 people, namely employees of Primagraha University. The results of this study in the first hypothesis there is a significant influence of communication on employee performance employee performance at Primagraha University in Serang City, obtained the results of t count > t table (2,677 > 2,024) then Ho was rejected and Ha diterma. With significant values, 0.011 < 0.05. The second hypothesis is that there is a significant influence of organizational culture on employee performance at Primagraha University in Serang City, with the results of t count > t table (6,067 > 2,024) then Ho is rejected and Ha diterma. With a significant value, 0.000 < 0.05, and the third hypothesis is that there is a significant influence of communication and organizational culture simultaneously on employee performance at Primagraha University in Seran City, obtained the results of F count > F table (35.531 > 3.25) then Ho was rejected. With significant values, 0.000 < 0.05. The conclusion of this study is that hypothesis one has a significant influence of Communication on Employee Performance at Primagraha University in Serang City, hypothesis two there is a significant influence of Organizational Culture on Employee Performance at Primagraha University in Serang City, and hypothesis three there is a significant influence of Communication and Organizational Culture on Employee Performance at Serang City.Primagraha University in Serang City.